Дослідження стійкості каналів управління дронів в умовах дії активних шумових завад різної поляризації - Душенков, О. В.; Мартинчук, О. О. (ХНУРЕ, 2025)
The paper investigates the stability of drone control channels under the influence of active noise interference of different polarization. The influence of signal polarization matching and interference on the quality of communication is analyzed. Methods for improving noise immunity, including adaptive antennas and digital signal processing, are considered. Vulnerability of systems with different types of polarization is assessed.
Keywords: канал управління дронів; шумові завади